Generic lightlike submanifolds of an indefinite Kaehler manifold with an (, m)-type metric connection - Lee, Chul Woo; Lee, Jae Won (Armenian Journal of Mathematics, 2020)
We study generic lightlike submanifolds M of an indefinite Kaehler manifold M or an indefinite complex space form M(c) with an (, m)-type metric connection subject such that the characteristic vector field ζ of M belongs to our screen distribution S(TM) of M.